Implementation of the Think Pair Share (TPS) Learning Model with the Assistance of Powerpoint Media in Science Learning for Fifth Grade Elementary School Students - Rosdiana Rosdiana; Supriyanto Supriyanto; Sujarwo Sujarwo (CV. Edujavare Publishing, 2026)
Learning is an interactive process between students, educators, and the learning environment to acquire knowledge, skills, understanding, and shape behavior changes according to learning goals. This study aims to determine the application of the Think Pair Share (TPS) learning model with the help of PowerPoint (PPT) media in science learning for fifth-grade students of SD Negeri I Pedang. This study uses a quantitative approach with the Pre-Experiment Design method and One Group Pretest-Posttest Design. The population and sample in this study amounted to 14 fifth-grade students of SD Negeri I Pedang, determined by saturated sampling techniques. Data collection techniques used include observation, interviews, documentation, and tests. Data analysis was carried out to determine student learning outcomes through calculating the average, standard deviation, normality testing using the Chi-Square test, and hypothesis testing using the T test at a significance level of 0.05. The results showed that the average pre-test score of students was 50, increasing to 81.35 in the post-test. The results of the hypothesis test obtained Thitung ≥ Ttabel (6.41 ≥ 1.77) so that Ho was rejected and Ha was accepted. Thus, it can be concluded that the application of the Think Pair Share (TPS) learning model with the assistance of PowerPoint (PPT) media in science learning for class V of SD Negeri I Pedang can be implemented well and is significantly able to achieve the Learning Objective Achievement Criteria (KKTP).